Testing the reliability and validity of the xos motion capture system at measuring counter movement vertical jump - Konz, S.; Cottrill, D. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study is to conduct simultaneous measurement of CMVJH using the XOS motion capture system and the Vertec system. Ten participants (body height: 170.17 cm ± 13.4, body weight: 79.76 kg ± 17.72) from the Marshall University student body comprised the testing group. Participants were instructed on proper CMVJ technique. Five practice jumps at 50% effort were conducted. Participants donned a compression suit with reflective markers. The paired t-tests indicated that a difference existed in CMVJ height measured between the Vertec and the XOS VJ was (p= .000), SEM of 1.4 with a .823 correlation and the Vertec and the XOS COG was also (p= .000), SEM of 1.42 with a correlation of .788. A marked difference exists between the XOS SportMotion capture system`s methods of measuring CMVJ height when compared to Vertec measurement.